2022
DOI: 10.1097/md.0000000000028972
|View full text |Cite
|
Sign up to set email alerts
|

Performance characterization of PCR-free whole genome sequencing for clinical diagnosis

Abstract: To evaluate the performance of polymerase chain reaction (PCR)-free whole genome sequencing (WGS) for clinical diagnosis, and thereby revealing how experimental parameters affect variant detection.Five NA12878 samples were sequenced using MGISEQ-2000. NA12878 samples underwent WGS with differing deoxyribonucleic acid (DNA) input and library preparation protocol (PCR-based vs PCR-free protocols for library preparation). The depth of coverage and genotype quality of each sample were compared. The performance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In general, DNA of reference samples (Coriell, Camden, NJ) and clinical samples with known variants (Additional file 1 : Table S1) were first extracted using the MagPure Tissue & Blood DNA KF Kit (Magen, China). Subsequently, one microgram of DNA was used to generate paired end reads of 150 bp/100 bp according to the PCR-free library preparation protocols and sequencing protocols [ 13 ]. The bioinformatics analysis pipeline included 4 sections for the detection of potential variants (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, DNA of reference samples (Coriell, Camden, NJ) and clinical samples with known variants (Additional file 1 : Table S1) were first extracted using the MagPure Tissue & Blood DNA KF Kit (Magen, China). Subsequently, one microgram of DNA was used to generate paired end reads of 150 bp/100 bp according to the PCR-free library preparation protocols and sequencing protocols [ 13 ]. The bioinformatics analysis pipeline included 4 sections for the detection of potential variants (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Some parameters (such as DNA input, read length and library preparation) may affect the performance of WGS and ultimately influence variation detection sensitivity. Our previous reports showed that PCR-free WGS with 1 µg DNA input exhibited a better depth of coverage and genotype quality distribution than PCR-based WGS with differing DNA inputs [ 13 ]. With respect to the depth of coverage (DP), a mean depth of 30–50X is the most widely used mean DP for WGS [ 6 , 14 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, WGS required a DNA amplification step, but with newer protocols this step is no longer needed. Omission of the amplification step eliminates the PCR-bias and provides a more uniform coverage and quality [ 12 ]. The library is generated by fragmenting the high molecular DNA followed by ligation of adapters that will bind to the linker DNA on the chip surface.…”
Section: Whole Genome Sequencingmentioning
confidence: 99%
“…Another reason for higher accuracy is the improvement in laboratory technologies. For example, it is nowadays standard to work with a PCR-free library preparation protocol, which outperforms PCR-based protocols (Zhou, Zhou, and Zeng 2022).…”
Section: Figure 18mentioning
confidence: 99%